Monocyte-macrophage activation is associated with nonalcoholic fatty liver disease and liver fibrosis in HIV monoinfection independently of the gut microbiome and bacterial translocation. - Maurice,JB; Garvey,L; Tsochatzis,EA; Wiltshire,M; Cooke,G; Guppy,N; McDonald,J; Marchesi,J; Nelson,M; Kelleher,P; Goldin,R; Thursz,M; et al. (AIDS, 2019)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) is common among people living with HIV. There are limited data available on the pathophysiology of NAFLD and the development of fibrosis in this population. OBJECTIVES: The aim of this study was to investigate the association of bacterial translocation, adipose tissue dysfunction, monocyte activation and gut dysbiosis in patients with HIV monoinfection and NAFLD. METHODS: Cases with biopsy-proven NAFLD and HIV monoinfection were age and sex-matched to HIV-positive and HIV-negative controls. Markers of bacterial translocation [lipopolysaccharide-binding protein (LBP), bacterial DNA and lipopolysaccharide (LPS)], adipose tissue dysfunction (leptin, adiponectin) and monocyte activation (sCD14 and sCD163) were measured by ELISA. Hepatic patterns of macrophage activation were explored with immunohistochemistry. 16s rRNA sequencing was performed with stool. RESULTS: Thirty-three cases were included (≥F2 fibrosis n=16), matched to HIV-positive (n=29) and HIV-negative (n=17) controls. Cases with NAFLD were more obese (BMI 31.0±4.4 vs. 24.1±2.8kg/m, P<0.001) and had significantly increased levels of sCD14, sCD163 and higher leptin to adiponectin ratio vs. HIV-positive controls. Cases with ≥F2 verses<F2 fibrosis had increased sCD14 (1.4±0.4 vs. 1.1±0.3μg/ml, P=0.023) and sCD163 (1.0±0.3 vs. 0.8±0.3μg/ml, P=0.060), which correlated with waist circumference (sCD14 P=0.022, sCD163 P=0.011). Immunohistochemistry showed increased hepatic portal macrophage clusters in patients with fibrosis. No markers of bacterial translocation or changes to the microbiome were associated with NAFLD or fibrosis. CONCLUSION: NAFLD fibrosis stage in HIV monoinfected patients is associated with monocyte activation in the context of obesity, which may be independent of bacterial translocation and gut microbiome.